A comparative study of lower grade and higher grade pupils at a Jewish community school with regard to intelligence, self-concept and adjustment - Reid, Cherry Lynn (Department of Social Development, 2016)
A comparison of Lower Grade and Higher Grade pupils with regard to intelligence, self-concept and adjustment. 29 Lower and 29 Higher grade pupils in Stds 8 and 9 at a Jewish community day school were compared with regard to their I Q scores, self-concepts and adjustment level. These variables were measured on the following tests: The NSAGT; the Piers-Harris Children's Self-Concept Scale and the PHSF Relations Questionnaire. The data from the two groups were compared by means of a t-test for small samples and the results demonstrated a significant difference (p≤0,01) for I Q scores and for self-concept but did not reveal a significant difference on most of the 12 sub-scales of the PHSF Relations Questionnaire. As regards the latter, a significant difference (p<0,05) was obtained on the sub-scale Sociability - S for female pupils and a significant difference was obtained on sub-scales Self-Confidence (p≤0,01) and Formal Relations (p≤0,05) for male pupils. The significant difference in I Q scores can be partially understood in terms of the selection criteria for admission to the Lower Grade class. The significant difference in self-concept can be attributed to the difference on the Intellectual and School Status sub-category. The lack of significant differences on the other sub-scales suggest that factors other than academic achievement are important in terms of self-concept formation for example:- class structure; membership of peer groups; extra-mural activities and family relationships. The lack of significant difference between Lower and Higher Grade pupils in the area of ,adjustment can perhaps be explained in terms of the Lower Grade pupils' relatively high scores on other sub-categories of the Piers-Harris Children's Self-Concept Scale i.e. it was only as regards intellectual status that the Lower Grade perceived themselves as less able.